Implementation of multicultural education through Sasambo Dance at the University of Mataram - Arif Widodo; Nursaptini Nursaptini; Muhammad Erfan (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
The risk of conflict on a multicultural campus is huge. Not a few conflicts between students who are motivated by cultural problems. Conflict prevention efforts can be done through multicultural education. One of the multicultural universities in Indonesia is the university of Mataram. This study aims to describe the implementation of multicultural education at the University of Mataram. The unit of analysis in this study is students of elementary school teacher education programs. This research is important to do considering the diverse cultural backgrounds of students. Students are always faced with cultural diversity within the university. This research was designed in the form of qualitative research. The approach used is ethnographic. The main problem examined in this study is how to apply multicultural education in PGSD study programs. The results of the study revealed that in implementing multicultural education in PGSD study programs using a local wisdom approach. One of them is through the Sasambo dance. Sasambo dance is a dance created by Sasak, Samawa, and Mbojo tribes. Sasambo dance is made an icon of PGSD. Each student is required to learn and take the meaning of the dance. The values contained in the Sasambo dance are the spirit of unity, cooperation, and equality. This dance illustrates the spirit of unity and equality of the three main ethnic groups in the province of West Nusa Tenggara. Through the Sasambo dance students are taught that each ethnic group has the same position. Mutual respect and respect for differences is the key. The implementation of multicultural education is important. Prospective elementary school teaching students in the future have a very important role in instilling the value of diversity of character in elementary schools.